Application of the Agropolitan Concept through Digital Marketing Training and Environmental Implications for MSMEs in Gunung Anyar District, Surabaya City - Harya, Gyska Indah; Mindari, Wanti; Setyadi, Taufik; Pratama, Arista; Mukaromah, Siti; Fadil, Cholid (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Gunung Anyar District in Surabaya focuses on agropolitan development to encourage regional economic growth, especially in agribusiness. Micro, Small, and Medium Enterprises (MSMEs) are important in improving the economy, reducing unemployment, and improving welfare. However, MSMEs face challenges with branding, digital marketing, and environmental impact. The community service program by UPN Veteran East Java aims to support the development of MSMEs through digitalization, product branding, and product diversification. The program also discusses environmental issues, including waste management and Urban Farming. Collaboration between local governments, MSMEs, and the community is essential for the success of this program. The program aims to overcome barriers such as low sales turnover and limited market access, strengthen the position of MSMEs in a competitive market, and become an example of sustainable business practices. The Lecturer Team conducts continuous socialization and assistance related to MSME skills in implementing digital marketing, training and mentoring "e-brilliant MSMEs" and maintaining cleanliness and preservation of the surrounding environment to reduce carbon footprint, increase green open space, and meet food needs through urban farming. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero hunger SDG 9: Industry, Innovation, and Infrastructure SDG 12: Responsible Consumption and Production SDG 13: Climate ActionSDG 15: Life on LandSDG 16: Peace, Justice, and Strong InstitutionsSDG 17: Partnerships for the Goals